Analisis Komunikasi Antarpribadi Melalui Gaya Kepemimpinan Melayani Kepala SMP Kristen Tomohon - Olivia Cherly Wuwung; Jeremia Engelita Wakas; Juanda Manullang (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to see and understand interpersonal communication through style serving leadership is carried out by the head of the Tomohon Christian Middle School. This research uses descriptive qualitative approach. By using servant leadership theory according to Greenleaf which describes ten factors of leadership serving, listening, empathy, restoration, awareness, persuasion, conceptualization, foresight, management, commitment to community growth, and building community. The method used in this research is qualitative research methods descriptive. The data procedure uses two sources, namely primary data obtained from interviews and secondary data obtained from literature studies. From the results research can be denied that the Principal of SMP Kristen Tomohon applies ten serving style leadership (servant leadership) according to Robert K. Greenleaf and This serving leadership style is very supportive of effective interpersonal communication. The results showed that statements of listening, recovery, awareness and persuasion in the context of serving leadership is also a stage in the process interpersonal communication carried out by the principal. The results showed There are two obstacles in the interpersonal communication run by the principal and the principals teachers or employees (subordinates), including understanding communication and service. Findings in this study shows that the application of style can serve minimize the obstacles that occur in the process of interpersonal communication between leaders with subordinates.